KNOWLEDGE MAPPING OF THREE READING COURSES FOR UNDERGRADUATE EFLTEP STUDENTS AT ONE INDONESIAN UNIVERSITY - Susanah, Susanah (Universitas Jambi, 2024)
This study aimed to identify how reading knowledge is constructed in three reading courses for EFLTEP students at one state university in Jambi and to investigate the degree of alignment between course content with the learning outcomes stipulated in the 2017 ELT curriculum implemented in that university and the 2013 ELT curriculum for secondary education. This study employed a content analysis by extracting information from the course syllabi. Data were gained solely from three sets of syllabi for Reading for General Purposes, Reading for Academic Purposes, and Critical Reading and Writing courses. The study showed that course content catered to the expected learning outcomes, although knowledge discrepancies and genres were overlapping among those three courses. It was also noticed that the contents were aligned with reading knowledge stipulated in the 2013 ELT curriculum as the courses continue to develop reading skills in terms of text structure, types, and comprehension level.